Contractual Savings, Capital Markets, and Firms' Financing Choices - Impavido, Gregorio (World Bank, Washington, DC, 2014)
The authors analyze the relationship between the development and asset allocation of contractual savings and firms' capital structures. The authors develop a simple model of firms' leverage and debt maturity decisions. They illustrate the mechanisms through which contractual savings development may affect corporate financing patterns. In the empirical section, the authors show that the development and asset allocation of contractual savings have an independent impact on firms' financing choices. Different channels are identified. In market-based economies, an increase in the proportion of shares in the portfolio of contractual savings leads to a decline in firms' leverage. In bank-based economies, instead, an increase in the size of contractual savings is associated with an increase in leverage and debt maturity in the corporate sector